The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12273-021-0836-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative distribution of human exhaled particles in a ventilation room

Abstract: Respiratory viruses can be attached to human exhaled particles and spread from person to person through respiratory activities. The purpose of this study is to obtain the quantitative description formula of human exhaled particles in the ventilated room through amount number of numerical simulation calculations and regression statistical analysis of the simulated data. In this study, a combination of numerical simulation and laboratory experiments was used, and the results were tallied preferably. Bacillus sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Pressure discretization was based on PRESTO! (pressure staggering option) 34,35 . The computations were considered to have converged when the scaled velocity and continuity residuals approached 10 −3 and the energy residuals reached 10 −6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure discretization was based on PRESTO! (pressure staggering option) 34,35 . The computations were considered to have converged when the scaled velocity and continuity residuals approached 10 −3 and the energy residuals reached 10 −6 .…”
Section: Methodsmentioning
confidence: 99%
“…(pressure staggering option). 34,35 The computations were considered to have converged when the scaled velocity and continuity residuals approached 10 −3 and the energy residuals reached 10 −6 . The governing equations were solved using the SIMPLE algorithm in the commercial CFD software ANSYS FLUENT 2021 R1.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Accordingly, both the propagation distance and the propagation area mentioned in this study were discriminated by the identifiable airflow boundary, whereas the nuclei of exhaled droplets in the real environment may have the ability to propagate much further. 43 , 44 Among the propagation distances, the diagonal distance, which can be calculated from horizontal and vertical directions, refers to the maximum visible length in the direction of propagation along the exhaled airflow.…”
Section: Resultsmentioning
confidence: 99%
“…The transmission of bioaerosols in the dental clinic was studied by both experimental research and numerical simulation, which is the most typical method to investigate bioaerosol concentrations ( Komperda et al, 2021 ; Liu et al, 2022 ; Polednik, 2021 ). A previous study reported that dental treatment causes a considerable increase in airborne bioaerosol concentrations in dental clinics, although the analyses were not comprehensive ( Dutil et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%